IMPROVING STUDENT'S VOCABULARY MASTERY USING FOOD PACKAGES VISUAL AIDS AT THE FIRST YEAR OF SMPN 4 SALATIGA - ILHAMI, ATIQ FIKRI (2011)
This research paper generally aims at improving the student's vocabulary mastery in learning English at Junior High School. The specific objective of this research is to describe procedures of improving student's vocabulary mastery using Food Packages Visual Aids and to know whether using Food Packages Visual Aids at Junior High School can improve the students' vocabulary mastery. In this research the writer carries out an action research. To collect the required data, the writer did observation, gave test, and used documentation. The writer draws planning, action, observation, and reflecting. There were two cycles in this action research in which each cycle used pre-test and post-test. He analyzed the data by comparing the result of pre-test and post-test. The results of pre-test and post-test were used to know the score of the vocabulary mastery. The result of the students' vocabulary mastery of pre-test I is 43.33 %, while the students' vocabulary mastery of post-test I is 73.33 %. The computation shows that the mean of the pre test I is 43.05 and the mean of the post test is 73.26 and also the students' vocabulary mastery of pre-test II is 46.66 %, while their vocabulary mastery of post-test II is 83.33 %. Besides the mean score of the pre test II is 46.35, while their mean score of post test II is 82.70. Based on the research finding, it can be concluded that the result of the students' mastery showed that Food Packages Visual Aids in teaching vocabulary could improve the students' participation and achievement better. The students' score was getting better in each cycle. It indicates that the teaching learning process was successful in which both the researcher and the students gained the objectives. Therefore, it is better for the students to study English carefully through practice and experience, and to be active and creative in learning English. While the English teacher should teach the students with Food Packages Visual Aids, process considerable knowledge to manage an interesting classroom, and prepare the lessons they are going to teach as well as possible.